PENGARUH VARIETAS TEBU, POTONGAN DAN PENUNDAAN GILING TERHADAP KUALITAS NIRA TEBU - Aries Diyanto Kuspratomo; Burhan Burhan; Muhammad Fakhry (AGROINTEK, 2012)
Sugar is a product produced by sugar cane (Saccharum officinarum).  The quality of sugar is measured by analysing Nira Perahan Pertama (NPP) of sugar cane.  Nira’s quality is influenced by sugar’s variety, sugar’s cutting, and sugarmill delay time.  The goal of this study is to know the influence of cutting sugar’s variety and sugarmill delay time toward nira’s quality (%brix, %pol, pH, reduction sugar %brix, HK and NNPP).  This study used completely randomized factorial design (RAL).  Some independent variables used are: sugar’s variety (PSJT 941 and PS 881), cutting sugar (without cutting, 1/3 partand 1/5 part), and sugarmill delay time (day 0/freshandday 3).  While dependent variable used in this study was nira’s quality: %brix, %pol, pH, reduction sugar %brix, HK and NNPP.  Data analysed by using 3 ways analysis of variance.  Comparation test was done using 5% significance level.  The study showed that the best variety was PS 881, 1/5 part cutting sugar was not influential significantly toward nira’s quality; sugarmill delay time in 3 days caused nira’s quality go down (shown by raise of %brix, decrease of pH, raise of reduction sugar %brix, and decrease of HK).